Molecular identification of methane-consuming bacteria in the Persian Gulf: a study for microbial gas exploration - Harirforoush, Mahsa; Shavandi, Mahmoud; Amoozegar, Mohammad Ali; Saffarian, Parvaneh; Hasrak, Shabnam (Frontiers in Microbiology, 2024)
The seepage of gaseous compounds from underground reservoirs towards the surface causes abnormalities in the population of microbial communities that consume light hydrocarbons on the surface of the reservoir. This microbial population can serve as indicators for determining the location of gas reservoirs prior to drilling operations. In this study, the simulation of methane gas leakage in the sediments of the Persian Gulf was conducted using a laboratory model. The objective of this simulation was to identify the microbial population consuming methane within the sediments of the Persian Gulf, aiding in the exploration of gas reserves. Continuous injection of methane gas into the system was performed for a period of 3 months to enrich the microbial consortia consuming methane. Subsequently, the microbial population was identified using next-generation sequencing (NGS) analysis. The results indicated that, based on the 16S rRNA sequencing dataset, aerobic methanotrophs, including genera Methylobacter, Methylomarinum, Methylomicrobium, Methylomonas, and Methylophage, were the dominant microbial group on the surface of the sediments. Additionally, anaerobic methane oxidation archaea in sediments were performed by ANME-2 and ANME-3 clades. The findings demonstrate that these microbial communities are capable of coexistence and thrive in long-term exposure to methane in the sediments of the Persian Gulf. Identifying this microbial pattern, alongside other geophysical and geological data, can increase the success rate of gas reservoir exploration.